Effect of non-nutritive sucking and leg massage on physiological and behavioral indicators of pain following heel blood sampling in term neonates - Mirzarahimi, Mehrdad; Mehrnoush, Nasrin; Shahizadeh, Sahife; Samadi, Nasrin; Amani, Firouz (International Journal of Advanced Nursing Studies, 2013)
Background: Pain management is especially important for neonates who are not able to verbally express their pain. Non-pharmacological pain management method as an alternative to pharmacological pain medication has increased nowadays. Objectives: The purpose of this study was to test the effect of leg massage and non-nutritive sucking (NNS) on reducing the pain that neonates experience when undergoing the heel stick procedure for blood testing. Methods: This investigation was a random controlled clinical trial study on ninety neonates who were selected randomly among admitted neonates to NICU in Alavi hospital at Ardabil. The subjects were randomly classified in two case and one control groups. The neonates received leg massage (n=30), NNS (n=30), and no intervention (n=30) respectively. Measurements of HR and SaO2 were taken twice: once before and then again after intervention. Pain response was measured by the PIPP scale. Results: The study showed that the HR of the three groups significantly increased after heel stick compared to before heel stick. The change of SaO2 levels in NNS groups was lower than the control and massage groups. The change of PIPP scores in massage and NNS groups was lower than that of the control group; however, there was not statistically significant differences between NNS & massage groups(p=0.91) Conclusion: pain management and pain relief in the infant is an important issue in neonatal health care. It is suggested that the single or combined use of massage and a pacifier is effective in reducing pain responses in neonates undergoing heel stick.